Functional insights of plant bcl-2–associated ahanogene (BAG) proteins: Multi-taskers in diverse cellular signal transduction pathways - Jiang, Hailong; Liu, Xiaoya; Xiao, Peixiang; Wang, Yan; Xie, Qihui; Wu, Xiaoxia; Ding, Haidong (Frontiers in Plant Science, 2023)
Bcl-2-associated athanogene (BAG) gene family is a highly conserved molecular chaperone cofactor in evolution from yeast to humans and plants playing important roles in a variety of signal pathways. Plant BAG proteins have special structures, especially those containing CaM-binding IQ motifs, which are unique to plants. While early studies focused more on the structure and physiological function of plant BAGs, recent studies have implicated many novel functional mechanisms involved in multiple cellular processes. How to achieve signal specificity has become an interesting topic of plant BAG research. In this review, we have provided a historic view of plant BAG research and summarized recent advances in the establishment of BAG as essential components in normal plant growth, environmental stress response, and plant immunity. Based on the relationship between BAG proteins and their newly interacting proteins, this review highlights the functional mechanisms of various cellular signals mediated by plant BAGs. Future work needs to focus on the post-translational modification of BAG proteins, and on understanding how specificity is achieved among BAG signaling pathways.